Exploring the gut microbiota of healthy captive Asian elephants from various locations in Yunnan, China - Wang, Yuhan; Wang, Yixuan; Zhou, Jiuxuan; Bao, Mingwei; Shah, Taif; Yang, Song; Zheng, Jing; Li, Qian; Hou, Yutong; Wang, Binghui; Yuan, Ruiling (Frontiers in Microbiology, 2024)
Introduction The Asian elephant (Elephas maximus) is a giant herbivore classified as an endangered wildlife species by the International Union for Conservation of Threatened Species.This study aims to investigate and compare the core gut microbiota of captive Asian elephants from three different locations in Yunnan Province, China, to explore the impact of environmental and husbandry factors on microbial diversity. Methods We collected fecal samples from 29 captive Asian elephants from three locations and performed full-length 16S rRNA gene sequencing. Microbial diversity was assessed using alpha diversity (Chao1 and Shannon indexes) and beta diversity (Bray-Curtis and Euclidean distance metrics). Principal coordinate analysis (PCoA) was used to visualize microbial variation among groups. Results Alpha diversity analysis showed that the microbial diversity in the Yexianggu group was higher than that in the other groups. Bray-Curtis and Euclidean metrics revealed significant differences among the microbial communities. Bacteroidetes and Firmicutes, which are key cellulose-degrading bacteria, were the dominant phyla in all groups. Synergistaceae was the most abundant family in the Menghai group, while Lachnospiraceae and Pirellulaceae were more abundant in the Yexianggu and Yuantongshan groups, respectively. Genus p-1008-a5-gut-group was more abundant in Yexianggu, and Prevotella was predominant in Menghai. Discussion These results indicate that habitat and husbandry practices significantly influence the gut microbiota of captive Asian elephants. The identification of bacterial species such as Lactobacillus fermentum, Clostridium neonatale, Enterococcus mundtii, Klebsiella huaxiensis, Corynebacterium nasicanis, and Streptococcus equinus highlights the potential role of specific microbes in maintaining host-microbial interactions. Promoting microbial diversity through improved captive conditions could enhance the health of these endangered animals.